Advanced Magnetic Nanostructures - Sellmyer, D.J.; Sellmyer, D.J.; Skomski, Ralph.; Skomski, Ralph. (Springer US : Imprint: Springer, 2006)
Advanced Magnetic Nanostructures is devoted to the fabrication, characterization, experimental investigation, theoretical understanding, and utilization of advanced magnetic nanostructures. Focus is on various types of 'bottom-up' and 'top-down' artificial nanostructures, as contrasted to naturally occurring magnetic nanostructures, such as iron-oxide inclusions in magnetic rocks, and to structures such as perfect thin films. Chapter 1 is an introduction into some basic concepts, such as the definitions of basic magnetic quantities. Chapters 2-4 are devoted to the theory of magnetic nanostructures, Chapter 5 deals with the characterization of the structures, and Chapters 6-10 are devoted to specific systems. Applications of advanced magnetic nanostructures are discussed in Chapters11-15 and, finally, the appendix lists and briefly discusses magnetic properties of typical starting materials. Industrial and academic researchers in magnetism and related areas such as nanotechnology, materials science, and theoretical solid-state physics will find this book a valuable resource.